KOMPARASI PENGAMPUAN (CURATELE) ANTARA INDONESIA DENGAN AMERIKA SERIKAT - Danindra Kurnia Dafa; Zakki Adlhiyati (Sebelas Maret University, 2023)
This article analyzes the comparison of guardianship or curatele between Indonesia and the United States. This article aims to determine the types and differences between guardianship (curatele) in Indonesia and the United States. The research method used in this article is a normative legal research method. This research has a descriptive research nature. The collection of legal materials is done by literature study with primary and secondary legal materials. Based on the results of the research, it can be concluded that there are differences between Indonesia and the United States, the differences are in the types of guardianship that exist in both countries, namely Indonesia and America. In Indonesia, a guardian (curator) usually only has rights and duties in accordance with what has been decided or determined by the Court at the time of the appointment of a guardian, while in the United States, guardianship is divided into 3, namely, guardianship of the person, guardianship of the estate, and guardian ad litem.Keywords: Comparison, Guardianship, Indonesia and United States